Herbicide and Application Timing Effects on Windmillgrass (Chloris verticillata) Control - Nicholas Mitchell; Jared Hoyle (Kansas Agricultural Experiment Station Research Reports, 2019)
Windmillgrass (Chloris verticillataNutt.) populations commonly infest turfgrass systems in the midwest, which result in aesthetically unacceptable turfgrass stands. Research trials were initiated in 2017 and 2018, in Onaga and Junction City, KS, to determine windmillgrass control with various single herbicide applications at different application timings. Pylex (topramezone) resulted in more than 80% windmillgrass control 8 weeks after spring and summer application.
Keywords: windmillgrass; weed control; herbicide efficacy; herbicide timing